Strong inhibition of M-Protease activity of Coronavirus by using PX-12 inhibitor based on ab initio ONIOM calculations. Issue 1 (January 2021) - Monajemi, Hadieh; Zain, Sharifuddin M
In this study, the interaction of seven potential inhibitors in complex with SARS-CoV-2's M protease (M pro ) is modelled and optimized using ONIOM (Own N-layered Integrated molecular Orbital and molecular Mechanics; QM/MM) approach. Density functional theory is used for the small system and Universal Force Field is used for the rest of the molecule with ONIOM (m062x/6-311++G (d, p):UFF) model chemistry. The seven inhibitors that are used in this study are N3, ebselen, disulfiram, tideglusib, carmofur, shikonin and PX-12. The calculated interaction energy between the inhibitor and M pro shows a strong inhibition of M pro activity with N3, ebselen as well as PX-12 inhibitors. The two former inhibitors are previously reported as strong inhibitors; however, the strong inhibition effect of PX-12 has not been previously reported. The results of this study can provide useful insight into designing an effective inhibitor drug for SARS-nCoV, suggesting a better inhibition from PX-12 than ebselen.